Vaccination of sheep and cattle against haemonchosis. Issue 5 (September 2015) - Bassetto, C.C.; Amarante, A.F.T.
Abstract Vaccines against gastrointestinal nematodes are one potential option for the control of parasitic gastroenteritis in ruminants. Excretory/secretory (E/S) and hidden antigens are being studied as candidates for vaccines against Haemonchus spp., which is a major parasite in cattle and small ruminants that are raised in warm climates. Protection has been observed after vaccination with some E/S proteases, particularly cysteine proteases and with some glycans that are abundant on the surfaces and in the secretory products of helminths. However, the most promising results are being obtained with glycoprotein antigens extracted from the microvillar surfaces of the Haemonchus contortus intestinal cells. These antigens are called 'hidden′ because they are not exposed to the host's immune system during infection. Thus far, recombinant forms of these antigens have not been usefully protective. However, because only 5 μg of antigen is required per dose, production of a native antigen vaccine from adult parasites has been found to be practical and commercially viable. Trials indicate that a vaccine made from one particular isolate will cross-protect against geographically distant isolates.